A Chorus of Cranes : The Cranes of North America and the World - Johnsgard, Paul A. (Book collections on Project MUSE., 2015)
"Accompanied by the stunning photography of Mangelsen, Johnsgard details the natural history, biology and conservation issues surrounding the abundant sandhill crane and the endangered whopping crane in North America"--